Manganese zinc ferrite composite material as well as internal mixing method and application thereof

By using the mixing of skeleton materials, binders, lubricants and antioxidants with manganese-zeb ferrite powder during the soft magnetic material refining process, the agglomeration and poor fluidity of particle size fine powder during the refining process is solved. The problem is that more uniform refining effect and higher product quality have been achieved.

CN119480321APending Publication Date: 2025-02-18HENGDIAN GRP DMEGC MAGNETICS CO LTD +1

Patent Information

Application Number
CN202411728901.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the soft magnetic material refining process, the finer manganese zinc ferrite powder has uneven mixing due to the tendency of agglomeration, poor fluidity, large material resistance, high energy consumption, low production efficiency and electrostatic effects, which affects product quality and Performance stability.

Method used

By mixing the skeleton material, binder, lubricant and antioxidant with a manganese zeolite powder with an average particle size D50 of 0.95μm-1.75μm, the synergistic effect of these additives is used to achieve manganese zeolite powder. The uniform dispersion of the intensive refining ensures uniformity and consistency.

Benefits of technology

Solve the problem of intensive refining difficulties caused by fine particle size of manganese zinc ferrite powder, improve the quality and performance stability of soft magnetic material injection molding products, promote large-scale production, and meet the market's high-performance soft magnetic material need.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159815120000201
    Figure BDA0005159815120000201
  • Figure BDA0005159815120000211
    Figure BDA0005159815120000211
Patent Text Reader

Abstract

The invention relates to a manganese zinc ferrite composite material as well as an internal mixing method and application thereof. The manganese zinc ferrite composite material comprises manganese zinc ferrite powder and an additive, the additives comprise a framework material, a binder, a lubricant and an antioxidant; the average particle size D50 of the manganese zinc ferrite powder is 0.95 [mu] m to 1.75 [mu] m. According to the invention, the additive comprising the framework material, the binder, the lubricant and the antioxidant is mixed with the manganese-zinc ferrite powder with the average particle size D50 of 0.95-1.75 [mu] m, and the manganese-zinc ferrite powder with the particle size can be uniformly dispersed in the manganese-zinc ferrite composite material under the combined action of the framework material, the binder, the lubricant and the antioxidant; and therefore, the uniform consistency of internal mixing is guaranteed, the problem that internal mixing is difficult due to the fact that the manganese zinc ferrite powder is small in particle size is solved, the quality of soft magnetic material injection molding products is improved, large-scale production is promoted, and the requirement of the market for high-performance soft magnetic materials is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of manganese-zinc-ferrite composite materials, in particular to a manganese-zinc-ferrite composite material and a mixing method and application thereof. Background Art

[0002] In today's rapidly developing electronics industry, soft magnetic materials, due to their unique magnetic properties, are widely used in various electronic devices, such as inductors and transformers. Injection molding of soft magnetic materials, with its advantages in producing complex shapes and achieving high-precision dimensional control, has gradually become the mainstream production method. As the performance requirements for soft magnetic materials continue to increase, finer soft magnetic powders are often used to achieve superior magnetic properties and a more uniform microstructure.

[0003] However, in the actual production process of soft magnetic material mixing, many problems arise in the mixing process due to the selection of soft magnetic powder with finer particle size. First, due to the finer particle size, it shows a strong tendency to agglomerate during the mixing process. These fine particles have extremely high surface energy and attract each other, making it difficult to disperse evenly in the injection molding matrix; second, the fluidity of the fine powder is extremely poor, which greatly increases the material resistance during the mixing process, and requires higher shear force and energy input to achieve effective mixing. This not only leads to a significant increase in the energy consumption of the mixing equipment, but also seriously affects production efficiency; third, the filling amount of the overly fine powder is too large, which compresses the space for other key ingredients, making the optimization and adjustment of the formula extremely difficult, which directly affects the quality and performance stability of the final injection molded product; in addition, electrostatic effect is also a problem that cannot be ignored. During the mixing process, the friction between the fine powders can easily generate static electricity, causing the powder to be adsorbed on the inner wall of the equipment and the stirring parts, further aggravating the uneven mixing.

[0004] CN111370198A discloses an injection-molded soft ferrite magnet and a preparation method thereof. The magnet comprises 80-93% soft ferrite magnetic powder, 0.1-1.0% magnetic powder surface modifier, 0.1-0.5% coupling agent, 0.2-0.8% surface organic insulating agent, 6-19% binder, and 0.1-1.0% flow aid. Phosphoric acid is used as the magnetic powder modifier. However, the reaction between phosphoric acid and the surface of the magnetic powder may change the surface structure and chemical composition of the magnetic powder to a certain extent, thereby adversely affecting the magnetic properties, such as reducing the magnetic permeability or changing the coercive force. Furthermore, the invention does not provide a solution to the problems encountered when using a soft magnetic powder with a finer particle size in the mixing process.

[0005] CN115772031A discloses a method for preparing a manganese-zinc ferrite magnetic spacer, which is prepared by mixing, crushing, injection molding, catalytic degreasing, and sintering to achieve densification. However, the invention uses a manganese-zinc ferrite powder with a particle size of 100-500 μm. Compared with micron-sized manganese-zinc ferrite powder, its mechanical and magnetic properties are lower, and it may also cause equipment wear and contamination of the product by equipment wear products. In addition, the invention uses paraffin wax and oleic acid as lubricants in the binder system, which are far less effective than polymer waxes. Furthermore, the invention does not address the problems encountered when using finer-particle soft magnetic powders during mixing.

[0006] Faced with the above-mentioned mixing difficulties caused by the fine particle size of soft magnetic powder, if they cannot be solved in a timely and effective manner, it will seriously restrict the quality improvement and large-scale production of soft magnetic material injection molding products, and will not be able to meet the market demand for high-performance soft magnetic materials.

[0007] Therefore, how to solve the difficulty of mixing manganese zinc ferrite powder due to its fine particle size has become an urgent problem to be solved, aiming to open up a new path for the development of soft magnetic material injection molding process. Summary of the Invention

[0008] In order to solve the above technical problems, the present invention provides a manganese-zinc ferrite composite material and its mixing method and application. The present invention mixes additives including a skeleton material, a binder, a lubricant and an antioxidant with a manganese-zinc ferrite powder with an average particle size D50 of 0.95μm-1.75μm. By utilizing the combined effect of the skeleton material, the binder, the lubricant and the antioxidant, the manganese-zinc ferrite powder with an average particle size D50 of 0.95μm-1.75μm can be evenly dispersed in the manganese-zinc ferrite composite material, thereby ensuring the uniformity of mixing and solving the problem of mixing difficulties caused by the fine particle size of manganese-zinc ferrite powder, thereby improving the quality of soft magnetic material injection molding products and promoting large-scale production, meeting the market demand for high-performance soft magnetic materials.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a manganese-zinc-ferrite composite material, wherein the manganese-zinc-ferrite composite material comprises manganese-zinc-ferrite powder and an additive;

[0011] The additives include skeleton materials, binders, lubricants and antioxidants;

[0012] The average particle size D50 of the manganese zinc ferrite powder is 0.95 μm-1.75 μm, for example, 0.95 μm, 1.00 μm, 1.05 μm, 1.10 μm, 1.15 μm, 1.20 μm, 1.25 μm, 1.30 μm, 1.35 μm, 1.40 μm, 1.45 μm, 1.50 μm, 1.55 μm, 1.60 μm, 1.65 μm, 1.70 μm or 1.75 μm, etc.

[0013] The manganese-zinc ferrite composite material provided by the present invention can make finer manganese-zinc ferrite powder uniformly dispersed in the manganese-zinc ferrite composite material by mixing manganese-zinc ferrite powder with an average particle size D50 of 0.95μm-1.75μm with the additive of the formula, thereby ensuring the uniformity and consistency of banburying, and solving the problems of difficulty in banburying caused by the fine particle size of manganese-zinc ferrite powder, easy agglomeration of manganese-zinc ferrite powder, and inability to ensure the structural uniformity of the prepared manganese-zinc ferrite composite material.

[0014] The present invention regulates the formula of the additives, wherein the skeleton material plays a role similar to a "skeleton" in the feed, providing basic structural strength and shape stability for the entire injection molded part (composite material). During the injection molding process, when the binder is removed in subsequent processes such as degreasing and sintering, the skeleton material can maintain the shape of the product and prevent it from collapsing and deforming. The addition of the binder gives the feed fluidity and can be wrapped around the surface of the manganese zinc ferrite powder particles during the mixing process, preventing the powder particles from agglomerating due to mutual attraction, so that the two are mixed evenly during continuous tumbling and collision under mechanical stirring. In addition, under the action of shear force, the agglomerates formed by the binder between the manganese zinc ferrite powder particles can be broken up, which can further promote the uniform dispersion of the manganese zinc ferrite powder and the binder. At the same time, by controlling the temperature and time of the mixing of the two, the binder molecules gradually diffuse around the powder particles due to thermal motion, fully contact with the powder and are evenly distributed on the surface, with uniform composition, and can further improve the quality stability of the manganese zinc ferrite composite material. The addition of an antioxidant can prevent the binder from oxidative decomposition and reduce the bonding effect, thereby extending the product's service life and maintaining stable performance. The addition of a lubricant can also achieve good lubrication and reduce friction between particles, allowing the entire feed to flow along a predetermined path under a certain pressure, achieving injection molding. The additive composed of the synergistic effect of the skeleton material, binder, lubricant, and antioxidant can ensure the uniformity of the manganese-zinc ferrite powder with an average particle size D50 of 0.95μm-1.75μm during the mixing process, making it evenly dispersed in the manganese-zinc ferrite composite material, thereby ensuring the uniformity of the mixing.

[0015] As a preferred technical solution of the present invention, the average particle size D50 of the manganese zinc ferrite powder is 1.0 μm-1.40 μm.

[0016] Preferably, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, the content of the manganese-zinc ferrite powder is 80wt%-85wt%, for example, 80wt%, 81wt%, 82wt%, 83wt%, 84wt% or 85wt%, etc., preferably 82wt%-85wt%.

[0017] Preferably, the skeleton material comprises polypropylene and high-density polyethylene.

[0018] In the present invention, polypropylene and high-density polyethylene are added together, and the synergistic effect can further improve the hardness and tensile strength of the manganese-zinc ferrite composite material.

[0019] Preferably, based on the total mass of the manganese-zinc ferrite composite material being 100wt%, the content of the polypropylene is 1wt%-3wt%, for example, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, etc., preferably 2wt%-3wt%.

[0020] Preferably, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, the content of the high-density polyethylene is 0.5wt%-1.5wt%, for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, etc., preferably 1wt%-1.5wt%.

[0021] Preferably, the binder comprises polyoxymethylene resin.

[0022] Preferably, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, the content of the polyformaldehyde resin is 10wt%-15wt%, for example, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, etc., preferably 11wt%-13wt%.

[0023] Preferably, the lubricant includes stearic acid and polymer wax.

[0024] In the present invention, stearic acid and polymer wax are added together as lubricants, which can further reduce the internal friction between the powder and the binder system during the mixing process, form a lubricating film between the various components of the feed, and make the various components move more smoothly during relative motion.

[0025] Preferably, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, the content of the stearic acid is 0.1wt%-1wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%, etc., preferably 0.1wt%-0.5wt%.

[0026] Preferably, the polymer wax includes polyamide wax or polyethylene wax.

[0027] Preferably, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, the content of the polymer wax is 0.5wt%-2wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, or 2wt%, etc., preferably 1wt%-2wt%.

[0028] Preferably, the antioxidant comprises a phosphite antioxidant.

[0029] In the present invention, the phosphite antioxidant can reduce the oxidative decomposition of the polyoxymethylene resin binder to the greatest extent, further extending the service life of the product and maintaining stable performance.

[0030] Preferably, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, the content of the phosphite antioxidant is 0.1wt%-0.5wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt% or 0.5wt%, etc., preferably 0.3wt%-0.5wt%.

[0031] In the present invention, by regulating the content of each component in the manganese-zinc ferrite composite material, the manganese-zinc ferrite powder with an average particle size D50 of 0.95 μm-1.75 μm can be better dispersed evenly in the manganese-zinc ferrite composite material, thereby further improving the comprehensive performance of the manganese-zinc ferrite composite material.

[0032] Preferably, the particle length of the manganese-zinc ferrite composite material is 2 mm-3 mm, for example, 2 mm, 2.2 mm, 2.4 mm, 2.6 mm, 2.8 mm or 3 mm.

[0033] In a second aspect, the present invention further provides a banburying method for the manganese-zinc ferrite composite material according to the first aspect, the banburying method comprising the following steps:

[0034] The manganese zinc ferrite powder is dispersed and pre-mixed to obtain a premix; the skeleton material, binder, lubricant and antioxidant are mixed with the premix and mixed to obtain a feed, which is granulated to obtain a manganese zinc ferrite composite material;

[0035] Wherein, the D50 average particle size of the manganese zinc ferrite powder is 0.95 μm-1.75 μm.

[0036] As a preferred technical solution of the present invention, the method of mixing the skeleton material, binder, lubricant and antioxidant with the premix and kneading the mixture comprises:

[0037] First, the skeleton material and the premix are mixed and subjected to a first banburying to obtain a first mixture; then, the binder, the antioxidant and the first mixture are mixed and subjected to a second banburying to obtain a second mixture; then, the lubricant and the second mixture are mixed and subjected to a third banburying to obtain a third mixture; then, the third mixture is subjected to a fourth banburying to obtain a feed material.

[0038] In the present invention, the skeleton material and the premix are first mixed and kneaded. Since the skeleton material has a certain spatial structure, it can provide a certain structural support for the entire feed. The components added later will diffuse and fill along this structure under the action of stirring, etc., thereby making it easier to achieve uniform mixing of the components in three-dimensional space and reduce the agglomeration of the premix. Then, a binder is added for kneading, which can better achieve the bonding effect and further improve the stability of product quality. Then, a lubricant is added for kneading, which can also achieve a good lubrication effect.

[0039] As a preferred technical solution of the present invention, the dispersion treatment method includes: firstly dispersing the manganese-zinc ferrite powder by mechanical dispersion, and then dispersing it by ultrasonic dispersion for a second time.

[0040] In the present invention, mechanical dispersion and ultrasonic dispersion are combined to reduce the occurrence of manganese zinc ferrite powder clustering in advance, which plays an auxiliary role in the subsequent mixing and kneading with additives.

[0041] Preferably, the pre-baking temperature is 150°C-170°C, for example, 150°C, 152°C, 154°C, 156°C, 158°C, 160°C, 162°C, 164°C, 168°C or 170°C, etc., preferably 150°C-160°C.

[0042] Preferably, the pre-mixing is forward rotation, and the forward rotation speed is 5 rpm-10 rpm, such as 5 rpm, 6 rpm, 7 rpm, 8 rpm, 9 rpm or 10 rpm.

[0043] Preferably, the pre-mixing time is 10 min-30 min, for example, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, etc., preferably 20 min-30 min.

[0044] In the present invention, since the manganese zinc ferrite powder with finer particle size may exhibit particle agglomeration or uneven particle size distribution during the preparation process, ultrasonic dispersion treatment is first performed and then pre-mixing is performed to break up these agglomerates, making the manganese zinc ferrite powder particles closer to the ideal state in size and shape, providing a basis for subsequent addition of additives and achieving better mixing effects.

[0045] Preferably, the temperature of the first mixing is 170-185°C, such as 170°C, 172°C, 174°C, 176°C, 178°C, 180°C, 182°C or 185°C, etc., preferably 170-175°C.

[0046] Preferably, the first internal kneading is forward rotation, and the forward rotation speed is 10 rpm-20 rpm, such as 10 rpm, 12 rpm, 14 rpm, 16 rpm, 18 rpm or 20 rpm.

[0047] Preferably, the first mixing time is 30 min-40 min, such as 30 min, 32 min, 34 min, 36 min, 38 min or 40 min.

[0048] Preferably, the first internal kneading is carried out under one stage of pressure.

[0049] As a preferred technical solution of the present invention, the temperature of the second mixing is 185°C-195°C, for example, 185°C, 186°C, 187°C, 188°C, 189°C, 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, etc., preferably 190°C-195°C.

[0050] Preferably, the second internal kneading is forward rotation, and the forward rotation speed is 20 rpm-30 rpm, such as 20 rpm, 22 rpm, 24 rpm, 26 rpm, 28 rpm or 30 rpm.

[0051] Preferably, the second mixing time is 30 min-40 min, such as 30 min, 32 min, 34 min, 36 min, 38 min or 40 min.

[0052] Preferably, the second internal mixing is carried out under two-stage pressure.

[0053] It should be noted that the mixing process in the present invention is carried out in an internal mixer. During the mixing process, the first stage of pressing refers to the hammer of the internal mixer being lowered to a certain height, but not in direct contact with the internal mixer rotor (powder to be mixed), and mixing and mixing are carried out in this state; the second stage of pressing refers to the hammer of the internal mixer being lowered to a certain height to be in direct contact with the internal mixer rotor (powder to be mixed), and mixing and mixing are carried out by continuously squeezing the powder to be mixed.

[0054] As a preferred technical solution of the present invention, the temperature of the third mixing is 185°C-195°C, for example, 185°C, 186°C, 187°C, 188°C, 189°C, 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, etc., preferably 190°C-195°C.

[0055] Preferably, the third internal kneading is forward rotation, and the forward rotation speed is 20 rpm-30 rpm, such as 20 rpm, 22 rpm, 24 rpm, 26 rpm, 28 rpm or 30 rpm.

[0056] Preferably, the third mixing time is 30 min-40 min, for example, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min.

[0057] Preferably, the third internal mixing is carried out under two-stage pressure.

[0058] As a preferred technical solution of the present invention, the temperature of the fourth internal mixing is 200°C-205°C, for example, 200°C, 201°C, 202°C, 203°C, 204°C or 205°C.

[0059] Preferably, the fourth internal kneading is reverse, and the reverse rotation speed is 40 rpm-45 rpm, such as 40 rpm, 41 rpm, 42 rpm, 43 rpm, 44 rpm or 45 rpm.

[0060] In the present invention, the combination of forward and reverse mixing can make the material flow direction in the mixing chamber no longer just move in a single direction, but be subjected to shear, extrusion and friction in all directions, thereby more fully mixing and ensuring uniform distribution of various components. In addition, the forward and reverse mixing method can also effectively break the component segregation trend caused by unidirectional rotation mixing, so that the material is always in a dynamic mixing state.

[0061] Preferably, the fourth mixing time is 60 min-80 min, for example, 60 min, 62 min, 64 min, 66 min, 68 min, 70 min, 72 min, 74 min, 76 min, 78 min or 80 min, etc., preferably 70 min-80 min.

[0062] Preferably, the fourth internal kneading is carried out under two-stage pressure.

[0063] Preferably, the granulation temperature is 150°C-170°C, for example, 150°C, 152°C, 154°C, 156°C, 158°C, 160°C, 162°C, 164°C, 168°C or 170°C.

[0064] As a preferred technical solution of the present invention, the banburying method comprises the following steps:

[0065] (1) firstly dispersing the manganese zinc ferrite powder by mechanical dispersion, and then dispersing it by ultrasonic dispersion for a second time, and pre-mixing the manganese zinc ferrite powder after the second dispersion at 150° C.-170° C. and a forward rotation speed of 5 rpm-10 rpm for 10 min-30 min to obtain a premix;

[0066] (2) mixing the skeleton material and the premix, and performing a first kneading process for 30 min to 40 min at a pressure of 170° C. to 185° C. and a forward rotation speed of 10 rpm to 20 rpm to obtain a first mixed material;

[0067] (3) mixing the binder, antioxidant and the first mixture, and kneading them for 30 min to 40 min under the conditions of a two-stage press at 185° C. to 195° C. and a forward rotation speed of 20 rpm to 30 rpm, and performing a second kneading to obtain a second mixture;

[0068] (4) mixing the lubricant and the second mixture, performing banburying for 30 min to 40 min under the conditions of a second-stage press at 185° C. to 195° C. and a forward rotation speed of 20 rpm to 30 rpm, and performing a third banburying to obtain a third mixture;

[0069] (5) kneading the third mixed material under the conditions of a second-stage press, 200° C.-205° C., and a reverse speed of 40 rpm-45 rpm for 60 min-80 min, performing a fourth kneading to obtain a feed, and heat-insulating and granulating at 150° C.-170° C. to obtain a manganese-zinc ferrite composite material;

[0070] Wherein, the D50 average particle size of the manganese zinc ferrite powder is 0.95 μm-1.75 μm.

[0071] In a third aspect, the present invention also provides an application of a manganese-zinc-ferrite composite material, wherein the manganese-zinc-ferrite composite material described in the first aspect, or the manganese-zinc-ferrite composite material obtained by mixing using the mixing method described in the second aspect, is applied to the field of consumer electronics or automotive electronics.

[0072] Compared with the prior art, the present invention has at least the following beneficial effects:

[0073] 1) The manganese-zinc ferrite composite material provided by the present invention is obtained by mixing manganese-zinc ferrite powder having an average particle size D50 of 0.95 μm-1.75 μm with additives including a skeleton material, a binder, a lubricant and an antioxidant. By utilizing the combined action of the skeleton material, the binder, the lubricant and the antioxidant, the manganese-zinc ferrite powder with a finer particle size can be evenly dispersed in the manganese-zinc ferrite composite material, thereby ensuring the uniform consistency of the mixing.

[0074] 2) The internal mixing method provided by the present invention disperses and pre-intermingles the manganese-zinc ferrite powder, and optimizes the order of adding additives and the forward and reverse rotation and rotation time of the internal mixer, thereby making the feed have strong fluidity, good dispersibility and low rubber content. The manganese-zinc ferrite prepared by the method has high mechanical strength and sintered density. DETAILED DESCRIPTION

[0075] For the convenience of understanding the present invention, the present invention is given below with examples. It should be understood by those skilled in the art that the examples are only for the purpose of helping to understand the present invention and should not be regarded as specific limitations of the present invention.

[0076] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0077] The method for preparing the manganese-zinc ferrite powder adopted in the specific embodiment of the present invention comprises the following steps:

[0078] Iron oxide, manganese oxide and zinc oxide are ball-milled once in a mass ratio of 73.4:21.8:4.8 to obtain a primary ball-milled material; the primary ball-milled material is pre-calcined at 800°C to obtain a pre-calcined material; the pre-calcined material is sequentially doped, ball-milled for a second time for 100 min-200 min and dried and sprayed to obtain the manganese-zinc ferrite powder. After measurement, the average particle size D50 of the manganese-zinc ferrite powder is 0.95 μm-1.75 μm.

[0079] Average particle size D50 of manganese zinc ferrite powder: the particle size corresponding to when the cumulative particle size distribution number of a powder sample reaches 50%, measured by Fisher permeability method, and the measuring instrument is HMK-22 average particle size analyzer.

[0080] Example 1

[0081] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof. Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 84 wt% of manganese-zinc ferrite powder, 2 wt% of polypropylene, 1 wt% of high-density polyethylene, 11.4 wt% of polyoxymethylene resin, 0.3 wt% of stearic acid, 1 wt% of polyamide wax, and 0.3 wt% of a phosphite antioxidant.

[0082] The banburying method comprises the following steps:

[0083] (1) Manganese zinc ferrite powder with a D50 of 1.0 μm was first dispersed using a high-speed mixer and then dispersed again using ultrasonic dispersion. The manganese zinc ferrite powder (84 wt%) after the second dispersion was pre-mixed at 150° C. and a forward rotation speed of 5 rpm for 20 min to obtain a 150° C. premix;

[0084] (2) 2 wt% of polypropylene, 1 wt% of high-density polyethylene, and the premix were mixed and kneaded for 30 min under the conditions of a primary press, 170° C., and a forward rotation speed of 10 rpm to obtain a first mixture;

[0085] (3) 11.4 wt% of polyoxymethylene resin, 0.3 wt% of phosphite antioxidant and the first mixture were mixed, and the mixture was kneaded for 40 min under the conditions of a two-stage press, 190° C., and a forward rotation speed of 20 rpm, and a second kneading was performed to obtain a second mixture;

[0086] (4) 0.3 wt % of stearic acid, 1 wt % of polyamide wax, and the second mixture were mixed, and the mixture was banburyed for 40 min under the conditions of a two-stage press, 190° C., and a forward rotation speed of 20 rpm, and a third banburying was performed to obtain a third mixture;

[0087] (5) The third mixed material was kneaded for 60 min under the conditions of a second-stage press, 200° C., and a reverse speed of 40 rpm, and a fourth kneading was performed to obtain a feed material, which was then heat-insulated and granulated at 155° C. to obtain a manganese-zinc ferrite composite material.

[0088] Example 2

[0089] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof. Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 82 wt% of manganese-zinc ferrite powder, 3 wt% of polypropylene, 1.5 wt% of high-density polyethylene, 12 wt% of polyoxymethylene resin, 0.5 wt% of stearic acid, 0.5 wt% of polyamide wax, and 0.5 wt% of a phosphite antioxidant.

[0090] The banburying method comprises the following steps:

[0091] (1) Manganese zinc ferrite powder with a D50 of 1.2 μm was first dispersed using a high-speed mixer and then dispersed again using ultrasonic dispersion. The manganese zinc ferrite powder (82 wt%) after the second dispersion was pre-mixed at 150° C. and a forward rotation speed of 5 rpm for 30 min to obtain a 150° C. premix;

[0092] (2) 3 wt% of polypropylene, 1.5 wt% of high-density polyethylene, and the premix were mixed and kneaded for 30 min under a first press at 170° C. and a forward rotation speed of 10 rpm to obtain a first mixture;

[0093] (3) 12 wt% of polyoxymethylene resin, 0.5 wt% of phosphite antioxidant and the first mixture were mixed, and the mixture was kneaded for 40 min under the conditions of a two-stage press, 195° C., and a forward rotation speed of 20 rpm, and a second kneading was performed to obtain a second mixture;

[0094] (4) 0.5 wt% of stearic acid, 0.5 wt% of polyamide wax, and the second mixture were mixed, and the mixture was banburyed for 30 min under the conditions of a two-stage press, 195° C., and a forward rotation speed of 20 rpm, and a third banburying was performed to obtain a third mixture;

[0095] (5) The third mixed material was kneaded for 80 min under the conditions of a second-stage press, 200° C., and a reverse speed of 40 rpm, and a fourth kneading was performed to obtain a feed material, which was then heat-insulated and granulated at 160° C. to obtain a manganese-zinc ferrite composite material.

[0096] Example 3

[0097] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof. Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 82 wt% of manganese-zinc ferrite powder, 2 wt% of polypropylene, 1 wt% of high-density polyethylene, 13 wt% of polyoxymethylene resin, 0.5 wt% of stearic acid, 1 wt% of polyamide wax, and 0.5 wt% of a phosphite antioxidant.

[0098] The banburying method comprises the following steps:

[0099] (1) Manganese zinc ferrite powder with a D50 of 1.1 μm was first dispersed using a high-speed mixer and then dispersed again using ultrasonic dispersion. The manganese zinc ferrite powder (82 wt%) after the second dispersion was pre-mixed at 160° C. and a forward rotation speed of 10 rpm for 20 min to obtain a 160° C. premix;

[0100] (2) 2 wt% of polypropylene, 1 wt% of high-density polyethylene, and the premix were mixed and kneaded for 30 min under the conditions of a primary press, 170° C., and a forward rotation speed of 10 rpm to obtain a first mixture;

[0101] (3) 13 wt% of polyoxymethylene resin, 0.5 wt% of phosphite antioxidant and the first mixture were mixed, and the mixture was kneaded for 40 min under the conditions of a two-stage press, 190° C., and a forward rotation speed of 20 rpm, and a second kneading was performed to obtain a second mixture;

[0102] (4) 0.5 wt % of stearic acid, 1 wt % of polyamide wax, and the second mixture were mixed, and the mixture was banburyed for 40 min under the conditions of a two-stage press, 190° C., and a forward rotation speed of 20 rpm, and a third banburying was performed to obtain a third mixture;

[0103] (5) The third mixed material was kneaded for 70 minutes under the conditions of a second-stage press, 200° C., and a reverse speed of 40 rpm, and a fourth kneading was performed to obtain a feed material, which was granulated at 160° C. to obtain a manganese-zinc ferrite composite material.

[0104] Example 4

[0105] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof. Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 83 wt% of manganese-zinc ferrite powder, 2 wt% of polypropylene, 1.5 wt% of high-density polyethylene, 11 wt% of polyoxymethylene resin, 0.2 wt% of stearic acid, 2 wt% of polyamide wax, and 0.3 wt% of a phosphite antioxidant.

[0106] The banburying method comprises the following steps:

[0107] (1) Manganese zinc ferrite powder with a D50 of 1.4 μm was first dispersed using a high-speed mixer and then dispersed again using ultrasonic dispersion. The manganese zinc ferrite powder (83 wt%) after the second dispersion was pre-mixed at 150° C. and a forward rotation speed of 10 rpm for 20 min to obtain a 150° C. premix;

[0108] (2) 2 wt% of polypropylene, 1.5 wt% of high-density polyethylene, and the premix were mixed and kneaded for 30 min under the conditions of a primary press, 175° C., and a forward rotation speed of 15 rpm to obtain a first mixture;

[0109] (3) 11 wt% of polyoxymethylene resin, 0.3 wt% of phosphite antioxidant and the first mixture were mixed, and the mixture was kneaded for 40 min under the conditions of a two-stage press, 190° C., and a forward rotation speed of 25 rpm, and a second kneading was performed to obtain a second mixture;

[0110] (4) 0.2 wt% of stearic acid, 2 wt% of polyamide wax, and the second mixture were mixed, and the mixture was kneaded for 35 min under the conditions of a two-stage press, 190° C., and a forward rotation speed of 25 rpm, and a third kneading was performed to obtain a third mixture;

[0111] (5) The third mixed material was kneaded for 80 min under the conditions of a second-stage press, 205° C., and a reverse speed of 40 rpm, and a fourth kneading was performed to obtain a feed material, which was heat-insulated and granulated at 160° C. to obtain a manganese-zinc ferrite composite material.

[0112] Example 5

[0113] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof. Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 84.8 wt% of manganese-zinc ferrite powder, 2 wt% of polypropylene, 1 wt% of high-density polyethylene, 11 wt% of polyoxymethylene resin, 0.1 wt% of stearic acid, 1 wt% of polyethylene wax, and 0.1 wt% of a phosphite antioxidant.

[0114] The banburying method comprises the following steps:

[0115] (1) Manganese zinc ferrite powder with a D50 of 1.0 μm was first dispersed using a high-speed mixer and then dispersed again using ultrasonic dispersion. The manganese zinc ferrite powder (84.8 wt %) after the second dispersion was pre-mixed at 155° C. and a forward rotation speed of 10 rpm for 25 min to obtain a 155° C. premix;

[0116] (2) 2 wt% of polypropylene, 1 wt% of high-density polyethylene, and the premix were mixed and kneaded for 40 min under the conditions of a primary press, 175° C., and a forward rotation speed of 15 rpm to obtain a first mixture;

[0117] (3) 11 wt% of polyoxymethylene resin, 0.1 wt% of phosphite antioxidant and the first mixture were mixed, and the mixture was kneaded for 30 min under the conditions of a second-stage press, 185° C., and a forward rotation speed of 30 rpm, and a second kneading was performed to obtain a second mixture;

[0118] (4) 0.1 wt% of stearic acid, 1 wt% of polyethylene wax, and the second mixture were mixed, and the mixture was banburyed for 30 min under the conditions of a two-stage press, 185° C., and a forward rotation speed of 30 rpm, and a third banburying was performed to obtain a third mixture;

[0119] (5) The third mixed material was kneaded for 70 min under the conditions of a second-stage press, 205° C., and a reverse speed of 45 rpm, and a fourth kneading was performed to obtain a feed material, which was heat-insulated and granulated at 170° C. to obtain a manganese-zinc ferrite composite material.

[0120] Example 6

[0121] This embodiment provides a manganese-zinc-ferrite composite material and a banburying method thereof. The components and contents of the manganese-zinc-ferrite composite material are consistent with those in Example 1.

[0122] The banburying method is different from that of Example 1 in that the temperature of the pre-banburying in step (1) is 130° C., the temperature of the first banburying in step (2) is 150° C., the temperature of the second banburying in step (3) is 170° C., the temperature of the third banburying in step (4) is 170° C., and the temperature of the fourth banburying in step (5) is 170° C. The remaining banburying methods and parameters are consistent with those of Example 1.

[0123] Example 7

[0124] This embodiment provides a manganese-zinc-ferrite composite material and a banburying method thereof. The components and contents of the manganese-zinc-ferrite composite material are consistent with those in Example 1.

[0125] The difference between the banburying method and Example 1 is that the time for the first banburying in step (2) is 20 minutes, the time for the third banburying in step (4) is 10 minutes, and the time for the fourth banburying in step (5) is 30 minutes. The other banburying methods and parameters are consistent with Example 1.

[0126] Example 8

[0127] This embodiment provides a manganese-zinc-ferrite composite material and a banburying method thereof. The components and contents of the manganese-zinc-ferrite composite material are consistent with those in Example 1.

[0128] The difference between the kneading method and Example 1 is that the fourth kneading in step (5) still uses the forward rotation method, and the other kneading methods and parameters remain consistent with Example 1.

[0129] Example 9

[0130] This embodiment provides a manganese-zinc-ferrite composite material and a banburying method thereof. The components and contents of the manganese-zinc-ferrite composite material are consistent with those in Example 1.

[0131] The difference between the banburying method and Example 1 is that the second banburying in step (3), the third banburying in step (4) and the fourth banburying in step (5) are all carried out under the condition of one-stage pressure, and the other banburying methods and parameters are consistent with Example 1.

[0132] Example 10

[0133] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein 0.3 wt % of the phosphite antioxidant in the manganese-zinc ferrite composite material is replaced with 0.3 wt % of a hindered phenol antioxidant, and the remaining components and contents remain the same as in Example 1;

[0134] The difference between the banburying method and Example 1 is that the phosphite antioxidant is replaced by an equal amount of hindered phenol antioxidant, and the other banburying methods and parameters are consistent with Example 1.

[0135] Example 11

[0136] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein high-density polyethylene is omitted from the manganese-zinc ferrite composite material. Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 84 wt% of manganese-zinc ferrite powder, 3 wt% of polypropylene, 11.4 wt% of polyoxymethylene resin, 0.3 wt% of stearic acid, 1 wt% of polyamide wax, and 0.3 wt% of a phosphite antioxidant.

[0137] The difference between the banburying method and Example 1 is that only 3 wt% of polypropylene is added to the skeleton material in step (2), and the rest of the banburying method and parameters are consistent with Example 1.

[0138] Example 12

[0139] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein the manganese-zinc ferrite composite material, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, comprises 82wt% of manganese-zinc ferrite powder, 3.5wt% of polypropylene, 2wt% of high-density polyethylene, 11wt% of polyoxymethylene resin, 0.2wt% of stearic acid, 1wt% of polyamide wax, and 0.3wt% of a phosphite antioxidant;

[0140] The difference between the banburying method and Example 1 is that the content of each component is adjusted according to the formula, and the other banburying methods and parameters are consistent with Example 1.

[0141] Example 13

[0142] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein the manganese-zinc ferrite composite material, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, comprises 83.45wt% of manganese-zinc ferrite powder, 0.5wt% of polypropylene, 0.25wt% of high-density polyethylene, 13wt% of polyoxymethylene resin, 0.5wt% of stearic acid, 2wt% of polyamide wax, and 0.3wt% of a phosphite antioxidant;

[0143] The difference between the banburying method and Example 1 is that the content of each component is adjusted according to the formula, and the other banburying methods and parameters are consistent with Example 1.

[0144] Example 14

[0145] This embodiment provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein the manganese-zinc ferrite composite material, based on the total mass of the manganese-zinc ferrite composite material as 100wt%, comprises 85wt% of manganese-zinc ferrite powder, 3wt% of polypropylene, 1.5wt% of high-density polyethylene, 8.5wt% of polyoxymethylene resin, 0.5wt% of stearic acid, 1wt% of polyamide wax and 0.5wt% of phosphite antioxidant;

[0146] The difference between the banburying method and Example 1 is that the content of each component is adjusted according to the formula, and the other banburying methods and parameters are consistent with Example 1.

[0147] Example 15

[0148] This embodiment provides a manganese-zinc-ferrite composite material and a banburying method thereof. The components and contents of the manganese-zinc-ferrite composite material are consistent with those in Example 1.

[0149] The banburying method differs from that of Example 1 in that equal amounts of polyoxymethylene resin and phosphite antioxidant are added in step (2), equal amounts of stearic acid and polyamide wax are added in step (3), and equal amounts of polypropylene and high-density polyethylene are added in step (4). The remaining banburying methods and parameters remain the same as those of Example 1.

[0150] Example 16

[0151] This embodiment provides a manganese-zinc-ferrite composite material and a banburying method thereof. The components and contents of the manganese-zinc-ferrite composite material are consistent with those in Example 1.

[0152] The banburying method differs from that of Example 1 in that equal amounts of stearic acid and polyamide wax are added in step (2), equal amounts of polypropylene and high-density polyethylene are added in step (3), and equal amounts of polyoxymethylene resin and phosphite antioxidant are added in step (4). The remaining banburying methods and parameters remain the same as those of Example 1.

[0153] Comparative Example 1

[0154] This comparative example provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein the manganese-zinc ferrite composite material comprises 79 wt % of manganese-zinc ferrite powder, 16 wt % of polyoxymethylene resin, 1 wt % of phosphite antioxidant, 1.5 wt % of polypropylene, and 0.5 wt % of stearic acid, and the remaining components and contents are the same as those in Example 1;

[0155] The difference between the banburying method and Example 1 is that the D50 of the manganese zinc ferrite powder in step (1) is 0.88 μm, and the content of each component is adjusted according to the formula. The other banburying methods and parameters are consistent with Example 1.

[0156] Comparative Example 2

[0157] This comparative example provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein the manganese-zinc ferrite composite material comprises 86.5 wt % of manganese-zinc ferrite powder, 10 wt % of polyoxymethylene resin, 0.7 wt % of high-density polyethylene, 1 wt % of polypropylene, and 0.5 wt % of stearic acid, and the remaining components and contents are the same as those in Example 1;

[0158] The difference between the banburying method and Example 1 is that the D50 of the manganese zinc ferrite powder in step (1) is 1.85 μm, the content of each component is adjusted according to the formula, and the other banburying methods and parameters are consistent with Example 1.

[0159] Comparative Example 3

[0160] This comparative example provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein polypropylene and high-density polyethylene (skeleton material) are omitted from the manganese-zinc ferrite composite material. Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 84.2 wt% of manganese-zinc ferrite powder, 13 wt% of polyoxymethylene resin, 0.5 wt% of stearic acid, 2 wt% of polyamide wax, and 0.3 wt% of a phosphite antioxidant;

[0161] The banburying method differs from that of Example 1 in that polypropylene and high-density polyethylene are omitted, the content of each component is adjusted according to the formula, and the remaining banburying methods and parameters remain the same as those of Example 1.

[0162] Comparative Example 4

[0163] This comparative example provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein the manganese-zinc ferrite composite material omits a phosphite antioxidant (antioxidant). Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 84 wt% of manganese-zinc ferrite powder, 2 wt% of polypropylene, 1 wt% of high-density polyethylene, 11.7 wt% of polyoxymethylene resin, 0.3 wt% of stearic acid, and 1 wt% of polyamide wax;

[0164] The banburying method differs from that of Example 1 in that the phosphite antioxidant is omitted, the content of each component is adjusted according to the formula, and the remaining banburying methods and parameters remain the same as those of Example 1.

[0165] Comparative Example 5

[0166] This comparative example provides a manganese-zinc ferrite composite material and a banburying method thereof, wherein stearic acid and polyamide wax (lubricant) are omitted from the manganese-zinc ferrite composite material. Based on the total mass of the manganese-zinc ferrite composite material being 100 wt%, the manganese-zinc ferrite composite material comprises 84 wt% of manganese-zinc ferrite powder, 2 wt% of polypropylene, 1 wt% of high-density polyethylene, 12.7 wt% of polyoxymethylene resin, and 0.3 wt% of a phosphite antioxidant;

[0167] The banburying method differs from that of Example 1 in that stearic acid and polyamide wax are omitted, the content of each component is adjusted according to the formula, and the remaining banburying methods and parameters remain the same as those of Example 1.

[0168] The manganese-zinc ferrite composite materials prepared in Examples 1-16 and Comparative Examples 1-5 were processed according to the size requirements of the test samples in each performance test, and the processed test samples were subjected to performance tests. The specific test conditions and standards (size requirements of the test samples) are as follows, and the specific test results are shown in Table 1.

[0169] 1) Melt flow index (MFI): An indicator that measures the melt flow properties of thermoplastics at specific temperature and pressure. It can reflect the processing fluidity of the feed and is tested in accordance with GB / T 3682 standard.

[0170] 2) Shore hardness: tested according to ASTM D2240 standard.

[0171] 3) Tensile strength: tested in accordance with GB / T528-2008 standard.

[0172] Table 1

[0173]

[0174]

[0175] Note: “ / ” indicates that the corresponding manganese-zinc ferrite composite material was not obtained and there is no performance test data.

[0176] The test results show that:

[0177] (1) It can be seen from Examples 1 to 5 that the present invention mixes additives including a skeleton material, a binder, a lubricant and an antioxidant with a manganese zinc ferrite powder having an average particle size D50 of 0.95 μm-1.75 μm, and utilizes the combined action of the skeleton material, the binder, the lubricant and the antioxidant to make the manganese zinc ferrite powder having an average particle size D50 of 0.95 μm-1.75 μm uniformly dispersed in the manganese zinc ferrite composite material. In addition, by dispersing and pre-mixing the manganese zinc ferrite powder, and optimizing the order of adding the additives and the forward and reverse rotation and rotation time of the mixer, the feed has strong fluidity, good dispersibility and low glue content. The manganese zinc ferrite prepared using the same has high mechanical strength and sintered density. Specifically, the melt index can reach 666.52 g / 10min-911.57 g / 10min, the hardness can reach 70A-80A, and the tensile strength can reach 6.0 MPa-7.5 MPa.

[0178] (2) It can be seen from Examples 6 and 7 that the present invention achieves the best banburying effect by further regulating the temperature and time of each banburying process, coordinating the banburying temperature and banburying time with each other. If the banburying temperature is low, it is not conducive to the flow and mixing of materials. If the banburying time is too short, the various components cannot be fully stirred, sheared and mixed.

[0179] (3) It can be seen from Example 8 that the present invention can further control the direction of the rotor of the internal mixer and perform all-round shearing and extrusion on the material by alternating forward and reverse rotation, so that the various components can be mixed more fully and evenly in the internal mixing chamber; in addition, forward and reverse rotation can achieve bidirectional plasticization and more uniform temperature distribution; while unilateral forward rotation can only achieve preliminary mixing and dispersion of the material, and cannot perform all-round shearing and extrusion and achieve bidirectional plasticization.

[0180] (4) It can be seen from Example 9 that the present invention further regulates the position of the pressure hammer, and retains some space between the mixed material and the pressure hammer during a period of pressing, so that the mixed material cannot be squeezed and broken up, and some materials are not fully mixed.

[0181] (5) It can be seen from Example 10 that the present invention further regulates the type of antioxidant and the selected phosphite antioxidant achieves the antioxidant effect by decomposing hydroperoxides and capturing free radicals; when replaced with a hindered phenol antioxidant, the feed flow becomes worse, which further indicates that the polyformaldehyde resin decomposes more and cannot inhibit the decomposition of the polyformaldehyde resin.

[0182] (6) It can be seen from Example 11 that the addition of high-density polyethylene of the present invention has a significant positive effect on promoting the improvement of the tensile strength of the manganese-zinc ferrite composite material. Its molecular chain can gradually straighten and withstand tension during the stretching process, thereby preventing the material from breaking prematurely and being able to withstand higher tensile forces. After omitting high-density polyethylene and using only polypropylene as the skeleton material, the overall strength and tensile strength are significantly reduced due to the sudden decrease in the tensile force-bearing component in the system.

[0183] (7) It can be seen from Examples 12 to 13 that the present invention further regulates the content of the skeleton material. The skeleton material usually has a higher molecular weight and molecular chain length. When the content is too high, the overall viscosity of the feed increases and the fluidity of the feed deteriorates; when the content is too low, the feed cannot maintain its shape during the injection molding process, especially when filling a mold cavity with a complex shape, it is easy to collapse or deform, thereby reducing its strength, stiffness and other properties.

[0184] (8) It can be seen from Example 14 that the present invention cannot achieve the encapsulation of powder particles by further reducing the content of polyoxymethylene resin, and thus cannot form agglomerates and granules.

[0185] (9) It can be seen from Examples 15 to 16 that the present invention can make the various additive components more evenly dispersed in the manganese zinc ferrite powder by further regulating the order of adding the various raw materials in the additive, thereby avoiding incompatibility between the various additive components or between the additive and the manganese zinc ferrite powder, and thus avoiding problems such as stratification and precipitation, which affect the quality of the mixing.

[0186] (10) It can be seen from Example 1 and Comparative Examples 1-2 that the additive formulation and banburying method of the present invention can be used to improve the banburying problem of manganese-zinc ferrite powder with an average particle size D50 of 0.95 μm-1.75 μm, and a better banburying effect can be obtained;

[0187] When the particle size of the manganese zinc ferrite powder is too small (Comparative Example 1), the surface energy between the particles increases, the mutual attraction is enhanced, and agglomeration is likely to occur. Even if an excessive amount of binder is added, it will be difficult to disperse evenly during the mixing process, which will lead to poor fluidity during the mixing process, affecting the transportation and filling of the material. On the other hand, the agglomerated position will become a weak point of the material, which is prone to breakage when subjected to external force.

[0188] When the particle size of the manganese zinc ferrite powder is too large (Comparative Example 2), the coarse powder will affect the mixing effect of the manganese zinc ferrite powder and other additives during the mixing process. The manganese zinc ferrite powder and additives usually need to be within a certain particle size range to achieve good mixing, and excessively coarse powder will destroy this balance. In addition, larger particles may not form a good bond with the binder and are prone to falling off or causing interface separation when subjected to force, thereby reducing the overall strength of the material.

[0189] It further shows that the formula and mixing method of the present application can better solve the problem of difficult mixing of manganese zinc ferrite powder with an average particle size D50 of 0.95μm-1.75μm.

[0190] (11) It can be seen from Example 1 and Comparative Examples 3-5 that the present invention further regulates the addition of four types of materials in the additives, including skeleton materials, binders, lubricants and antioxidants, to achieve synergistic effects, thereby improving the fluidity of the feed and enhancing the strength, hardness, uniformity and durability of the manganese-zinc ferrite composite material.

[0191] In summary, the present invention mixes additives including a skeleton material, a binder, a lubricant and an antioxidant with a manganese-zinc ferrite powder with an average particle size D50 of 0.95μm-1.75μm. By utilizing the combined effect of the skeleton material, the binder, the lubricant and the antioxidant, the manganese-zinc ferrite powder with an average particle size D50 of 0.95μm-1.75μm can be evenly dispersed in the manganese-zinc ferrite composite material, thereby ensuring the uniformity of the mixing, solving the problem of mixing difficulties caused by the fine particle size of the manganese-zinc ferrite powder, and thus improving the quality of soft magnetic material injection molding products and promoting large-scale production, thereby meeting the market demand for high-performance soft magnetic materials.

[0192] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. A manganese-zinc ferrite composite material, characterized in that: The manganese-zinc-ferrite composite material comprises manganese-zinc-ferrite powder and additives; The additives include skeleton materials, binders, lubricants and antioxidants; The average particle size D50 of the manganese zinc ferrite powder is 0.95 μm-1.75 μm.

2. The manganese-zinc ferrite composite material according to claim 1, characterized in that: The average particle size D50 of the manganese zinc ferrite powder is 1.00 μm-1.40 μm; Preferably, based on the total mass of the manganese-zinc-ferrite composite material being 100wt%, the content of the manganese-zinc-ferrite powder is 80wt%-85wt%, preferably 82wt%-85wt%; Preferably, the skeleton material comprises polypropylene and high-density polyethylene; Preferably, based on the total mass of the manganese-zinc ferrite composite material being 100wt%, the content of the polypropylene is 1wt%-3wt%, preferably 2wt%-3wt%; Preferably, based on the total mass of the manganese-zinc ferrite composite material being 100wt%, the content of the high-density polyethylene is 0.5wt%-1.5wt%, preferably 1wt%-1.5wt%; Preferably, the binder comprises polyoxymethylene resin; Preferably, based on the total mass of the manganese-zinc ferrite composite material being 100wt%, the content of the polyoxymethylene resin is 10wt%-15wt%, preferably 11wt%-13wt%; Preferably, the lubricant includes stearic acid and polymer wax; Preferably, based on the total mass of the manganese-zinc ferrite composite material being 100wt%, the content of the stearic acid is 0.1wt%-1wt%, preferably 0.1wt%-0.5wt%; Preferably, the polymer wax includes polyamide wax or polyethylene wax; Preferably, based on the total mass of the manganese-zinc ferrite composite material being 100wt%, the content of the polymer wax is 0.5wt%-2wt%, preferably 1wt%-2wt%; Preferably, the antioxidant comprises a phosphite antioxidant; Preferably, based on the total mass of the manganese-zinc ferrite composite material being 100wt%, the content of the phosphite antioxidant is 0.1wt%-0.5wt%, preferably 0.3wt%-0.5wt%; Preferably, the particle length of the manganese-zinc ferrite composite material is 2 mm-3 mm.

3. A method for mixing the manganese-zinc ferrite composite material according to claim 1 or 2, characterized in that: The mixing method comprises the following steps: The manganese-zinc-ferrite powder is dispersed and pre-kneaded to obtain a premix; the skeleton material, binder, lubricant and antioxidant are mixed with the premix and kneaded to obtain a feed, which is granulated to obtain a manganese-zinc-ferrite composite material; Wherein, the average particle size D50 of the manganese zinc ferrite powder is 0.95 μm-1.75 μm.

4. The banburying method according to claim 3, characterized in that: The method of mixing the skeleton material, the binder, the lubricant and the antioxidant with the premix for kneading comprises: First, the skeleton material and the premix are mixed, and the first internal kneading is performed to obtain a first mixture; then, the binder, the antioxidant and the first mixture are mixed, and the second internal kneading is performed to obtain a second mixture; then, the lubricant and the second mixture are mixed, and the third internal kneading is performed to obtain a third mixture; then, the third mixture is subjected to a fourth internal kneading to obtain a feed material.

5. The banburying method according to claim 4, characterized in that: The dispersion treatment method includes: firstly dispersing the manganese-zinc ferrite powder by mechanical dispersion, and then dispersing it by ultrasonic dispersion for a second time; Preferably, the pre-baking temperature is 150°C-170°C, preferably 150°C-160°C; Preferably, the pre-mixing is forward rotation, and the forward rotation speed is 5rpm-10rpm; Preferably, the pre-mixing time is 10 min-30 min, preferably 20 min-30 min; Preferably, the temperature of the first banburying is 170°C-185°C, preferably 170°C-175°C; Preferably, the first internal kneading is forward rotation, and the forward rotation speed is 10rpm-20rpm; Preferably, the first kneading time is 30min-40min; Preferably, the first internal kneading is carried out under one stage of pressure.

6. The banburying method according to any one of claims 4 to 5, characterized in that: The temperature of the second internal kneading is 185°C-195°C, preferably 190°C-195°C; Preferably, the second internal kneading is forward rotation, and the forward rotation speed is 20rpm-30rpm; Preferably, the second kneading time is 30min-40min; Preferably, the second internal kneading is carried out under two-stage pressure.

7. The banburying method according to any one of claims 4 to 6, characterized in that: The temperature of the third internal kneading is 185°C-195°C, preferably 190°C-195°C; Preferably, the third internal kneading is forward rotation, and the forward rotation speed is 20rpm-30rpm; Preferably, the third kneading time is 30min-40min; Preferably, the third internal kneading is carried out under two-stage pressure.

8. The banburying method according to any one of claims 4 to 7, characterized in that: The temperature of the fourth internal kneading is 200°C-205°C; Preferably, the fourth internal kneading is reverse, and the reverse rotation speed is 40rpm-45rpm; Preferably, the fourth kneading time is 60min-80min, preferably 70min-80min; Preferably, the fourth internal kneading is carried out under two-stage pressure; Preferably, the granulation temperature is 150°C-170°C.

9. The banburying method according to claim 3, characterized in that: The mixing method comprises the following steps: (1) firstly dispersing the manganese zinc ferrite powder by mechanical dispersion, and then dispersing it by ultrasonic dispersion for a second time, and pre-mixing the manganese zinc ferrite powder after the second dispersion at 150° C.-170° C. and a forward rotation speed of 5 rpm-10 rpm for 10 min-30 min to obtain a premix; (2) mixing the skeleton material and the premix, and kneading them for 30 min to 40 min at a first stage of pressing, 170° C. to 185° C., and a forward rotation speed of 10 rpm to 20 rpm to obtain a first mixture; (3) mixing the binder, the antioxidant and the first mixed material, and kneading them for 30 min to 40 min under the conditions of a two-stage press, 185° C. to 195° C., and a forward rotation speed of 20 rpm to 30 rpm, and performing a second kneading to obtain a second mixed material; (4) mixing the lubricant and the second mixed material, performing banburying for 30 min-40 min under the conditions of a two-stage press, 185° C.-195° C., and a forward rotation speed of 20 rpm-30 rpm, and performing a third banburying to obtain a third mixed material; (5) kneading the third mixed material under the conditions of two-stage pressing, 200° C.-205° C., and reverse speed 40 rpm-45 rpm for 60 min-80 min, performing a fourth kneading to obtain a feed material, and heat-preserving and granulating at 150° C.-170° C. to obtain a manganese-zinc ferrite composite material; Wherein, the average particle size D50 of the manganese zinc ferrite powder is 0.95 μm-1.75 μm.

10. An application of a manganese-zinc ferrite composite material, characterized in that: The manganese-zinc-ferrite composite material according to claim 1 or 2, or the manganese-zinc-ferrite composite material obtained by banburying according to any one of claims 3 to 9, is applied to the field of consumer electronics or automotive electronics.

Citation Information

Patent Citations

  • Injection-molded soft magnetic ferrite magnet and preparation method thereof

    CN111370198A

Cited By

  • MnZn ferrite feed for injection molding, preparation method of MnZn ferrite feed, magnetic core and preparation method of magnetic core

    CN120413222A